2016
DOI: 10.20882/adicciones.831
|View full text |Cite
|
Sign up to set email alerts
|

Dosis de metadona y su relación con calidad de vida, satisfacción, psicopatología, rendimiento cognitivo y consumo adicional de sustancias no prescritas

Abstract: The effectiveness of methadone maintenance treatment is beyond any doubt, but there remains some incertitude about the appropriate and effective dosage and the objectives that should be achieved by this therapy. Some authors maintain that only doses higher than 50-60 mg/day ought to be considered effective, since only these block all the opioid receptors. But others propose the use of doses adjusted to the needs of the patient, based on their recovery process. ADICCIONES, 2017 · VOL. 29 NÚM. 1 38 Dosis de meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
1
0
2
Order By: Relevance
“…In this review, a considerable number of studies have been found to refer to the more advanced age of substance users worldwide, as well as of people in treatment with opiate replacement drugs not specific to methadone (Carlsen et al, 2019). The articles found in Spanish, such as the study by Bobes & Bobes, refer to the long-term effectiveness of methadone treatment but not to the people undergoing this treatment (Bobes García & Bobes Bascarán, 2012); others, such as Quimbayo or Roncero et al, refer to the considerations regarding older adults who are consumers of substances in general (Quimbayo Díaz, 2018;Roncero et al, 2011), including a recommendation for long-term or indefinite housing resources or the need for coordination between public administrations (Lagares Roibás et al, 2010); or, as in the article by Pedrero-Pérez, refer to the long-term effect of methadone on patients' quality of life according to the doses they take (Pedrero-Pérez & MethaQoL, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, a considerable number of studies have been found to refer to the more advanced age of substance users worldwide, as well as of people in treatment with opiate replacement drugs not specific to methadone (Carlsen et al, 2019). The articles found in Spanish, such as the study by Bobes & Bobes, refer to the long-term effectiveness of methadone treatment but not to the people undergoing this treatment (Bobes García & Bobes Bascarán, 2012); others, such as Quimbayo or Roncero et al, refer to the considerations regarding older adults who are consumers of substances in general (Quimbayo Díaz, 2018;Roncero et al, 2011), including a recommendation for long-term or indefinite housing resources or the need for coordination between public administrations (Lagares Roibás et al, 2010); or, as in the article by Pedrero-Pérez, refer to the long-term effect of methadone on patients' quality of life according to the doses they take (Pedrero-Pérez & MethaQoL, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a los programas de PMM en usuarios de drogas por vía parenteral, son estadísticamente más frecuentes en malos adherentes en el análisis bruto, pero no resulta significativa esta asociación en el análisis multivariante. Este hallazgo difiere de los sugerido por otros autores (Malta, Strathdee, Magnanini y Bastos, 2008), y podría deberse a que, en nuestra muestra, el perfil de paciente en PMM se corresponde con un peor nivel socioeconómico y situación clínica, lo cual sería congruente con los hallazgos de otros estudios (Martínez-Luna et al, 2018;Pedrero-Pérez y Grupo MethaQoL, 2017).…”
Section: Discussionunclassified
“…Los programas de tratamiento de mantenimiento con metadona (TMM) han demostrado ser eficaces para reducir el uso ilícito de opioides, y el riesgo de infección por el virus de la inmunodeficiencia humana (VIH) y/o virus de la hepatitis C (VHC), entre otras variables (Kleber, 2008;Pedrero-Pérez y MethaQoL, 2017).…”
unclassified